Can Professional Development Improve School Leadership? Results From a Randomized Control Trial Assessing the Impact of McREL's Balanced Leadership Program on Principals in Rural Michigan Schools. (October 2016) - Miller, Robert James; Goddard, Roger D.; Kim, Minjung; Jacob, Robin; Goddard, Yvonne; Schroeder, Patricia
Purpose: This multiyear experimental study was designed to examine (1) the causal impact of McREL International's Balanced Leadership® Professional Development (BLPD) program on school principals' learning, beliefs, and behaviors and (2) whether there were differences in the types of outcomes the professional development influenced. Outcomes included principals' reported sense of efficacy, perceptions of school climate, and leadership behaviors.Research Methods: Approximately 100 school principals in rural Michigan were randomly assigned to either a treatment group that was offered 2 years of BLPD training or a control group that conducted business as usual. We employed principal survey data from the first and third years of the School Leadership Improvement Study. The treatment effect on each outcome was assessed through regression analysis, which controlled for baseline scores and school demographics.Findings: Results from the School Leadership Improvement Study show that BLPD participants reported substantively significant growth on the majority of the outcomes targeted by the program. Interestingly, treatment principals were more likely to report growth on broad, school-level outcomes than in areas that involved them working directly with teachers.Implications: This evaluation demonstrates that the McREL Balanced Leadership program caused gains in the majority of knowledge, belief, and behavior outcomes with the largest impacts on principals' sense of efficacy for instructional improvement, reported ability to bring about change, and strength of norms for teachers' instructional practice. The authors explore possibilities for why broad, school-level outcomes were more likely to be affected than areas that involve principals more directly in teachers' work.